SOSIALISASI UU ITE TENTANG JUDI ONLINE DAN PENCEGAHANNYA BAGI SISWA SMA NEGERI 7 PANDEGLANG - Husin Rianda; Dodi Irawan; Ari Azhari; Sayyidina Mufakkar; Fadhil Habibi; Davi Putra Stiawan (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
Online gambling has become a growing digital risk for students because it often appears through social media, online games, digital advertisements, links, bonuses, and promotional content resembling entertainment. This community service program focused on preventing online gambling among students at SMA Negeri 7 Pandeglang by strengthening legal awareness, digital literacy, religious values, and character education. The purpose of this program was to educate students about the risks, legal consequences, and moral implications of online gambling. This activity used an Asset-Based Community Development approach through the stages of Discovery, Dream, Design, Define, and Destiny. Data were collected through observation, question-and-answer sessions, discussion, reflection, and documentation, then analyzed descriptively. The results showed that students had initial exposure to online gambling but limited understanding of its digital forms and legal consequences. The program improved students’ awareness of online gambling risks and positioned the school as a strategic asset for sustainable prevention.